Advancing Ocular Drug Delivery: Harnessing Nanogels to Overcome Limitations and Enhance Therapeutic Efficacy - Aravindraj M; P.N. Remya; N. Damodharan (The Bioscan, 2026)
The delivery of therapies for ocular diseases has a broader range of medications, but the administration of drugs is often limited by the anatomical and physiological barriers. This review aims to critically evaluate the translational potential of nanogel-based ocular drug delivery systems (ODD), with a focus on addressing clinical applicability, long-term safety, and scalability while providing a comparative perspective against existing ocular drug delivery systems. In this review, we collected data through a search of peer-reviewed articles in the PubMed database released between 2020 and 2025. Here, we analyzed the common barriers that affect the ocular drug delivery system, conventional methodologies, nanogel drug delivery methods, formulation techniques, and therapeutic methods of nanogel. We have observed that the ODD nanogels have an increased penetration rate, superior precorneal retention, and controlled drug delivery of anterior and posterior segment ailments. Other modern methods, such as stimuli-responsive formulations, hybrid nanogel nanoparticle assemblies, and bioadhesive surface modification, have demonstrated potential in enhancing therapeutic targeting and stability. Nevertheless, issues with long-term safety validation, batch-to-batch reproducibility, and compliance with regulatory standards remain. The effectiveness, safety, and clinical relevance of nanogel-based ocular therapeutics have high potential in changing the face of ocular therapeutics.